2005
DOI: 10.1162/1054746053890242
|View full text |Cite
|
Sign up to set email alerts
|

The Responses of People to Virtual Humans in an Immersive Virtual Environment

Abstract: This paper presents an experiment investigating the impact of behavior and responsiveness on social responses to virtual humans in an immersive virtual environment (IVE). A number of responses are investigated, including presence, copresence, and two physiological responses-heart rate and electrodermal activity (EDA). Our findings suggest that increasing agents' responsiveness even on a simple level can have a significant impact on certain aspects of people's social responses to humanoid agents.Despite being a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 17 publications
3
119
0
Order By: Relevance
“…Users are inclined to feel empathetic with animated virtual characters (Morrison & Ziemke, 2005) and tend to feel as though they are in a social situation when a computer-animated character is displayed (Garau, Slater, Pertaub, & Razzaque, 2005). Likewise, studies show that characteristics of other virtual characters, such as gender (Guadagno, Blascovich, Bailenson, & McCall, 2007), or aspects of the interpersonal RUNNING HEAD: Virtual Violence and Guilt 6 virtual setting, such as interpersonal distance (Bailenson, Blascovich, Beall, & Loomis, 2003), influence the way users perceive and interact with these characters socially.…”
Section: Different From Playing Chess: the Moral Significance Of Virtmentioning
confidence: 99%
“…Users are inclined to feel empathetic with animated virtual characters (Morrison & Ziemke, 2005) and tend to feel as though they are in a social situation when a computer-animated character is displayed (Garau, Slater, Pertaub, & Razzaque, 2005). Likewise, studies show that characteristics of other virtual characters, such as gender (Guadagno, Blascovich, Bailenson, & McCall, 2007), or aspects of the interpersonal RUNNING HEAD: Virtual Violence and Guilt 6 virtual setting, such as interpersonal distance (Bailenson, Blascovich, Beall, & Loomis, 2003), influence the way users perceive and interact with these characters socially.…”
Section: Different From Playing Chess: the Moral Significance Of Virtmentioning
confidence: 99%
“…It has been shown that virtual human appearance and behavior can impact measures of social presence in immersive environments [1,38], as well as influence user behavior and perceptions of personal contact during the experience [11]. Further, within educational contexts, Kim and Baylor have found that the use, gender and appearance of virtual humans can affect student attitudes about math and hard science disciplines [18].…”
Section: Virtual Humansmentioning
confidence: 99%
“…The virtual reality and human factors communities use the notion of presence to describe users' perception of transportation into a virtual environment [11,16,28,36,42]. This definition also points to presence as a useful construct for describing the types of experiences audiences report when feeling transported into a story.…”
Section: Introductionmentioning
confidence: 99%
“…People will respond to virtual humans in a more realistic way when those virtual humans respond to them more realistically (Garau, Slater, Pertaub & Razzaque, 2005). The sense is that the technology still has a ways to go before people will respond to virtual humans in the same way but this may change as people have more experience with immersive environments.…”
Section: Virtual Humansmentioning
confidence: 99%
“…It's not that training systems don't exist but that they could be vastly improved (see results from Tromp et al, 2003). The issues are different if the training system is supposed to supply the other team members (virtual humans; see Garau et al, 2005) or whether all the real human team members will be represented in the virtual environment for training. This last possibility would allow for distance team training in a virtual environment.…”
Section: Future Directionsmentioning
confidence: 99%